DC Motor Speed Control Using LDR Sensor and Atmega89s52 (International Journal of Engineering and Computer Science, 2016)
In robotic applications DC Motor control is very common. Other than it there are many applications  that have been developed based on motor control in electronic field such as in automation, Flexible Manufacturing System (FMS) and Computer Integrated Manufacturing (CIM). The purpose of this project is to control the speed of DC motor depending on the light intensity falling on an LDR using microcontroller.